1993
DOI: 10.1046/j.1365-313x.1993.04020317.x
|View full text |Cite
|
Sign up to set email alerts
|

A 330 bp region of the spinach nitrite reductase gene promoter directs nitrate‐inducible tissue‐specific expression in transgenic tobacco

Abstract: Nitrite reductase is an enzyme in the nitrate assimilatory pathway whose expression is induced upon the addition of nitrate. Furthermore, it is known to be located in chloroplasts in leaves and plastids in roots. A 3.1 kb 5′ upstream region of the spinach nitrite reductase (NiR) gene promoter was shown previously to confer nitrate inducibility on the β‐glucuronidase (GUS) reporter gene expression in both the leaves and the roots of transgenic tobacco plants. In the present study, this 3.1 kb promoter fragment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 0 publications
0
30
0
1
Order By: Relevance
“…This problem can also be overcom? by genninating T2 seeds directly on ammonium medium a s described by Rastogi et al (1993) in analysis of nitrate induction on NiR. Whether the differences between our resultj and those of Vaucheret et al (1992) result from differences in the reporter gene, plant species, and/or the experimental protocol used for nitrate induction remains unclear.…”
Section: Dlscusslonmentioning
confidence: 85%
See 1 more Smart Citation
“…This problem can also be overcom? by genninating T2 seeds directly on ammonium medium a s described by Rastogi et al (1993) in analysis of nitrate induction on NiR. Whether the differences between our resultj and those of Vaucheret et al (1992) result from differences in the reporter gene, plant species, and/or the experimental protocol used for nitrate induction remains unclear.…”
Section: Dlscusslonmentioning
confidence: 85%
“…It is generally agreed that NiR genes are expressed at a higher leve1 than NR genes (Layzell, 1990). Deletion analysis of the spinach NiR promoter revealed that a 330-bp 5' flanking region is sufficient in achieving high levels of expression in the presence of nitrate (Rastogi et al, 1993).…”
Section: Rp07035-25 and Gm46116 Jb Was Supported By Nih Geneticsmentioning
confidence: 99%
“…Presumably eis-acting elements and truns-acting inducer protein(s) are required for NR induction. A 130-bp region of the spinach NiR promoter located between -330 and -200 is essential for induction of NiR gene expression in transgenic tobacco plants (Rastogi et al, 1993). However, this region of the NiR gene has no discernible conservation with 5' upstream DNA sequences of NR genes (Rastogi et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Promoter analysis of bean (Sander et al 1995), spinach (Rastogi 1993, Neininger et al 1994, Sivasankar et al 1998 tobacco (Dorbe et al 1998) and birch (Warning and Hachtel 2000) have revealed cis-acting elements involved in nitrate induction of NII transcription. Promoter analysis was performed by linking the promoters, or promoter fragments, to a reporter gene, and introducing this into tobacco, or in one case (Dorbe et al 1998) Arabidopsis.…”
Section: Nii Promotersmentioning
confidence: 99%